Effects of sociodemographic characteristics and patients' health beliefs on tuberculosis treatment adherence in Ethiopia: a structural equation modelling approach - Habteyes Hailu Tola; Mehrdad Karimi; Mir Saeed Yekaninejad (BMC, 2017)
Abstract Background Patients' beliefs are a major factor affecting tuberculosis (TB) treatment adherence. However, there has been little use of Health Belief Model (HBM) in determining the pathway effect of patients' sociodemographic characteristics and beliefs on TB treatment adherence. Therefore, this study was aimed at determining the effect of sociodemographic characteristics and patients' health beliefs on TB treatment adherence based on the HBM concept in Ethiopia. Methods A cross-sectional study was conducted in Addis Ababa, Ethiopia among TB patients undertaking treatment. Thirty health centres were randomly selected and one hospital was purposely chosen. Six hundred and ninety-eight TB patients who had been on treatment for 1-2 month, were aged 18 years or above, and had the mental capability to provide consent were enrolled consecutively with non-probability sampling technique from the TB registration book until required sample size achieved. Structured questionnaires were used to collect data. Structural equation modelling was employed to assess the pathway relationship between sociodemographic characteristics, patients' beliefs, and treatment adherence. Results Of the 698 enrolled participants, 401 (57.4%) were male and 490 (70.2%) were aged 35 years and below. The mean age of participants was 32 (± 11.7) and the age range was 18-90 years. Perceived barrier/benefit was shown to be a significant direct negative effect on TB treatment adherence (ß = −0.124, P = 0.032). In addition, cue to action (ß = −0.68, P ≤ 0.001) and psychological distress (ß = 0.08, P < 0.001) were shown significant indirect effects on TB treatment adherence through perceived barrier/benefit. Conclusions Interventions intended to decrease perceived barriers and maximize perceived benefits should be implemented to enhance TB treatment adherence. In addition, it is crucial that counselling is incorporated with the regular directly observed therapy program. Motivators (cue to actions) such as friends, family, healthcare workers, and the media could be used to promote TB treatment adherence.